Towards a methodology for analyzing ethnological prehispanic Andean Art and Performances - Arana Bustamante, Luis (2012)
I do here a revision of main theoretical orientations employed in study and interpretation of Andean prehispanic art. It is worth to be noted that this theme conceived in proper terms includes aspects such the architectural planning and design, which I would study in a forthcoming communication. As a preliminary part of the application of an ethnological study of the theme, I noted in this anterior article that these representations reflect and are constructed from the cosmological concepts of peoples an individuals that have made them. So, I examine the ethnological earlier treatments of this issue and some aspects and consecuences of the apliccation of a proposed conceptualization of culture (Arana Bustamante 2011) to this broad theme. but I do not advance a formulation of these broad cosmological principles in this ocassion, for reasons of order of exposition and the limited lenght of an article. Instead of it, I expose here a methodological discussion, a proposition of the ways to combine the different perspectives about the genesis of symbolism an a formulation of the ways in which the proposed ‘stratigraphic’ conceptualization of culture - that integrates the crucial factor of time and historical transformation-, had permitted to me: a) to essay a proof of this method in the ordenation of diverse evidence of this kind, b) to make more controled comparation, clasification and diferentiation of the evidences c) to formulate a number of preliminary interpretations of these evidence